REVIEWING ANTI-MALARIAL USAGE AND RESISTANCE PATTERNS AND ITS EFFECTS ON WORLD HEALTH ORGANISATION PROGRAMS - Nikolce Kocovski; William Godfrey L. L. B; Derek Elkington B. Sc; Christopher Weir B. Sc (Российский паразитологический журнал)
The two most significant strains of human malaria parasites responsible for morbidity and mortality are  Plasmodium falciparum  and  P. vivax. One issue, which further compounds treatment of these pathogens, is one of drug resistance. Drug resistance often emerges from key mutations selected for by inadequate treatment regimes and has shown to be able to spread globally, further compounding the development of newer and more effective drug treatment programs, such as those from the World Health Organisation (WHO). Here we review the historical usage of anti-malarial drugs, the development of resistance in Africa and Asia, mechanisms of drug action and resistance, and the effects of resistance on WHO policy.